Uncovering multilayered vulnerability and resilience in rural villages in the Pacific: a case study of Ono Island, Fiji - Daniela Medina Hidalgo (Resilience Alliance, 2021)
Peripheral communities across the Pacific are progressively being recognized as priority areas for the implementation of climate change adaptation strategies. A key step in planning and implementing effective adaptation actions is to identify what elements are driving vulnerability and resilience. Building on existing vulnerability and resilience conceptual models, we developed and applied a conceptual framework to identify drivers of vulnerability and resilience in social-ecological systems. By unifying the two concepts of vulnerability and resilience into a single framework, it is possible to better capture drivers of coping, adaptive and transformative capacities, and how they relate to specific climate hazards. The aim of the framework is to provide the conceptual basis from which the two concepts can be applied in conjunction, rather than prescribing specific indicators. The proposed framework was applied using a participatory action research approach to identify drivers of resilience and vulnerability in three coastal villages on a peripheral rural island in Fiji. Results from the framework's application show that these communities are currently contextualized within multiple layers of vulnerability and resilience, driven by: dependency on external support to implement activities, lack of knowledge about novel management actions for dealing with rapid environmental change, high levels of agency, increased access to support and services, high levels of awareness about climate change impacts, disposition to implement change and learn, and capacity to mobilize community resources and support. The development and application of the framework highlights aspects of vulnerability and resilience that have been overlooked or undervalued in the past when designing and implementing strategies for climate change adaptation in small island developing states (SIDS). The proposed framework has the potential to help overcome existing barriers in designing and implementing successful adaptation strategies, optimizing their effectiveness and sustainability in ways that are aligned with the unique situations of many SIDS.